Immunoglobulin-mediated immune dysregulation in recurrent pregnancy loss: mechanisms, biomarkers, and therapeutic perspectives - Kamala C; Pallavi Shekar; Umme Kulsum; Ananya Hegde; Lakshitha V Jayakrishna; Deepa Bhat; Meghana Hangala Shivakumaraswamy; Akila Prashant; Praveen Kumar K S (Immunologic Research, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disease that is typified by repeated pregnancy loss with immune dysregulation emerging as a critical contributing factor. Immunoglobulins are among the immune components that are instrumental in preserving tolerance between the mother and the fetus, regulating inflammatory responses, and supporting placental development. This review provides a comprehensive overview of the role of immunoglobulins in recurrent pregnancy loss, with particular emphasis on immune dysregulation, emerging biomarkers, and therapeutic implications. The immunoglobulin profiles, such as the changes in IgG subclasses and the presence of pathogenic autoantibodies, e.g. antiphospholipid and antinuclear antibodies, are highly correlated with unfavourable pregnancy outcomes. These changes, in a mechanistic manner, lead to poor trophoblast invasion, endothelial dysfunction, thrombosis and cytokine imbalance. Emerging evidence also highlights the contribution of regulatory B cells and the antibody-mediated immune network in maintaining pregnancy homeostasis. Immunoglobulin profiling has clinical potential as a diagnostic and prognostic methodology that can be used to stratify patients and provide customised therapy. Immunomodulatory therapies, especially intravenous immunoglobulin (IVIG), are potentially effective in a limited range of patient populations, but clinical response is variable. On the whole, this review demonstrates the role of immunoglobulin-mediated mechanisms in RPL and their future potential in enhancing precision medicine approaches to better diagnosis and management.

Oral delivery of an ustekinumab biosimilar with bioavailability comparable to subcutaneous administration in healthy human participants - Joshua T. Myers; Alyson Yamaguchi; Kyle Horlen; Leonard C. Fung; April Toledo Vo; Deepa Mohan; Mary Hoopes; Mir Imran; Jacques Van Dam; Ofer M. Gonen; Mir A. Hashim; Arvinder K. Dhalla; et al. (European Journal of Clinical Pharmacology, 2026)

Fluoroquinolone Resistant Enterobacteriaceae Isolated from Bagmati River and its Tributaries in Kathmandu, Nepal - Santosh Khanal; Joshna Thapa; Deepa Neupane; Suman SK; Sudeep K C; Tista Prasai Joshi; Dev Raj Joshi (Water, Air, & Soil Pollution, 2026)

The influence of climate modes on long-term sea level variability of the Indian ocean with special emphasis on the Southern Annular Mode: A study based on Indian ocean sea level reconstructions - J. S. Deepa; C. Gnanaseelan; K. V. Anusree (Theoretical and Applied Climatology, 2025)

Genetic diversity and population structure analysis in tamarind (Tamarindus indica L.) using SCoT and SRAP markers - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; D. C. Lakshmana Reddy; K. Prakash (Genetic Resources and Crop Evolution, 2025)

Development of dual stress-tolerant rice variety Jyothi with Saltol and Sub1 genes through marker-assisted backcross breeding - Deepa John; P. C. Rohini; K. S. Shylaraj (Cereal Research Communications, 2024)

Phenotypic diversity in Tamarindus indica L. sourced from different provenances in India - C. Kanupriya; G. Karunakaran; Pritee Singh; R. Venugopalan; Deepa Samant; K. Prakash (Agroforestry Systems, 2024)

Investigation of Kinetic Drug Release Characteristics and In Vitro Evaluation of Sustained-Release Matrix Tablets of a Selective COX-2 Inhibitor for Rheumatic Diseases - M. Karthikeyan; M. K. Deepa; E. Bassim; C. S. Rahna; K. R. Sree Raj (Journal of Pharmaceutical Innovation, 2021)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

The influence of diesel—truck exhaust particles on the kinetics of the atmospheric oxidation of dissolved sulfur dioxide by oxygen - Vimlesh Kumar Meena; Yogpal Dhayal; Deepa Saxena; Ashu Rani; C. P. Singh Chandel; K. S. Gupta (Environmental Science and Pollution Research, 2016)

Growth enhancement of black pepper (Piper nigrum) by a newly isolated Bacillus tequilensis NII-0943 - Syed G. Dastager; C. K. Deepa; Ashok Pandey (Biologia, 2011)

Paracoccus niistensis sp. nov., isolated from forest soil, India - Syed G. Dastager; C. K. Deepa; Wen-Jun Li; Shu-Kun Tang; Ashok Pandey (Antonie van Leeuwenhoek, 2011)

Potential plant growth-promoting activity of Serratia nematodiphila NII-0928 on black pepper (Piper nigrum L.) - Syed G. Dastager; C. K. Deepa; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2011)

Plant growth-promoting activity in newly isolated Bacillus thioparus (NII-0902) from Western ghat forest, India - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Isolation and characterization of plant growth promoting bacteria from non-rhizospheric soil and their effect on cowpea (Vigna unguiculata (L.) Walp.) seedling growth - C. K. Deepa; Syed G. Dastager; Ashok Pandey (World Journal of Microbiology and Biotechnology, 2010)

Structure of the extended diarrhea-inducing domain of rotavirus enterotoxigenic protein NSP4 - R. Deepa; C. Durga Rao; K. Suguna (Archives of Virology, 2007)

Phosphate starvation responses are mediated by sugar signaling in Arabidopsis - Athikkattuvalasu S. Karthikeyan; Deepa K. Varadarajan; Ajay Jain; Michael A. Held; Nicholas C. Carpita; Kashchandra G. Raghothama (Planta, 2007)